2018
DOI: 10.1177/0268355518771225
|View full text |Cite
|
Sign up to set email alerts
|

ClariVein™ – One year results of mechano-chemical ablation for varicose veins in a multi-ethnic Asian population from Singapore

Abstract: Early results are similar to what is described so far in the mechano-chemical ablation literature but recurrences are more than expected at one year. This is disappointing but is tempered by the fact that the majority of patients were asymptomatic and required no reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Gibson and Ferris showed similar degree of patient satisfaction and very low pain scores in their WAVES study, 10 which is comparable to MOCA. 20,21 Reasons for this are that VSCS and MOCA are performed without tumescent anaesthesia and requires only one injection with local anaesthesia at the injection site. Furthermore, there is no potential risk of thermal-related injuries to surrounding nerves or tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Gibson and Ferris showed similar degree of patient satisfaction and very low pain scores in their WAVES study, 10 which is comparable to MOCA. 20,21 Reasons for this are that VSCS and MOCA are performed without tumescent anaesthesia and requires only one injection with local anaesthesia at the injection site. Furthermore, there is no potential risk of thermal-related injuries to surrounding nerves or tissues.…”
Section: Discussionmentioning
confidence: 99%
“…28 Our results have also shown that Asians tend to have more concomitant GSV and SSV reflux. If treating both simultaneously, which has been the trend in Singapore, 16 perhaps would favour the use of an NTNT technique, where venous reflux can be treated with little risk to the adjacent superficial nerves, i.e. saphenous nerve for the GSV and sural nerve for the SSV.…”
Section: Discussionmentioning
confidence: 99%
“…15 Our own data from Singapore have shown that the truncal saphenous veins tend to be smaller in diameter and may well lend itself nicely for NTNT ablation to allow easier vein closure with a more minimally invasive technique compared to EVLA or RFA. 16 The aim of this study is to investigate whether there are differences between Caucasian and Asians from two disparate cohorts in the world, with regard to their pre-operative venous reflux patterns and truncal vein characteristics, which could potentially help clinicians tailor venous treatment on a more individualised basis in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum daily doses for sclerosant injection shall be observed. In several case series and non-randomised studies, high initial occlusion rates and little pain were reported [170][171][172][173][174][175].…”
Section: Mechanochemical Endovenous Ablation (Moca)mentioning
confidence: 99%